Gastronomi Kuliner Ayam Panggang Mbak Dhenok - Sri Purnaningsih (TOBA: Journal of Tourism, Hospitality, and Destination, 2024)
The culinary offering of grilled chicken, famously known as Ayam Panggang Mbak Dhenok, is a distinctive specialty of Karanganyar, poised to become a primary attraction in the realm of gastronomic tourism. The flavorful essence of Ayam Panggang Mbak Dhenok serves as the key motivator for individuals to visit, allowing them to relish new experiences and sample food and beverages that will create enduring memories of their travels. This research aims to analyze economic growth and creative tourism, with a specific focus on gastronomic cuisine, especially Ayam Panggang Mbak Dhenok in Karanganyar. The research method employed is qualitative with a descriptive approach. Data collection involves primary data gathered through observation, interviews, and documentation. The results of field interviews will be organized and presented descriptively. Secondary data is obtained from a literature review, including journals and articles relevant to the research. The research findings demonstrate that Ayam Panggang Mbak Dhenok has significant potential to emerge as a leading attraction in the culinary tourism sector, making a substantial contribution to the local economy. The uniqueness of its cooking methods, exceptional presentation, and authentic flavor have made this dish widely popular and appealing to a diverse range of visitors. Strengthening the role of Ayam Panggang Mbak Dhenok as a culinary tourism asset can easily be realized in the vicinity of the reservoir, offering a culinary experience that holds high educational, economic, and social value.